REFLECTIVE ANALYSIS OF FALLS IN THE SAFETY OF PATIENTS ON DIALYSIS - Onislene Alves Evangelista de Almeida; Maria Cristina Soares Rodrigues; Walterlânia Silva Santos (Universidade Federal do Paraná, 2016)
The purpose of this study was to present a reflective analysis of falls and its singularities in chronic kidney disease and dialysis treatment on the basis of publications on the topic. It was observed that chronic kidney disease and dialysis add some particularities to the prediction of the risk of falls. Qualified interventions in the identification of risk and prevention of complications associated with this event are crucial. Studies that explain the mechanisms of interaction between falls and dialysis treatment are scarce, therefore new studies are necessary to develop an instrument that is effective for the stratification of the risk of falls.